2023
DOI: 10.1128/spectrum.05364-22
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Spread of the Mobilized RND Efflux Pump Gene Cluster tmexCD-toprJ in Klebsiella pneumoniae from Different Sources

Abstract: Tigecycline has been regarded as one of the last-resort antibiotics available for the treatment of infections caused by carbapenem-resistant Enterobacterales . The plasmid-mediated resistance-nodulation-division–type efflux pump gene cluster tmexCD - toprJ is a newly identified tigecycline resistance determinant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This insertion event may be of great importance in the transferability and evolution of resistance genes (Wang et al, 2017). It has been reported that tmexCD1-toprJ1 has disseminated among K. pneumoniae strains from different sources, such as poultry, food markets, and patients, and is located on plasmids or chromosomes (Sun et al, 2023). Its orthologous variants, tmexCD2-toprJ2, tmexCD3-toprJ3, and tmexCD4-toprJ4, were reported in various species of Enterobacteriaceae, while the plasmid types were different from Frontiers in Microbiology 07 frontiersin.org pK82-tmexCD-toprJ.…”
Section: Discussionmentioning
confidence: 99%
“…This insertion event may be of great importance in the transferability and evolution of resistance genes (Wang et al, 2017). It has been reported that tmexCD1-toprJ1 has disseminated among K. pneumoniae strains from different sources, such as poultry, food markets, and patients, and is located on plasmids or chromosomes (Sun et al, 2023). Its orthologous variants, tmexCD2-toprJ2, tmexCD3-toprJ3, and tmexCD4-toprJ4, were reported in various species of Enterobacteriaceae, while the plasmid types were different from Frontiers in Microbiology 07 frontiersin.org pK82-tmexCD-toprJ.…”
Section: Discussionmentioning
confidence: 99%